The “revolving door” or the circulation of leaders between the economic and political fields of power in Mexico - Julia Chardavoine (Íconos)
By studying the professional trajectories of 276 senior and elected officials and of 486 business leaders within fifteen economic groups listed in the index of the Mexican Stock Exchange, this article studies the revolving door phenomenon in Mexico between 2000 and 2016. It shows that there is mainly a one-way revolving door in the country, from private companies to the State and not vice-versa and analyzes the multiple forms of investment of the political-administrative field of power by the business leaders in the country, taking into account the structural diversity of the economic field of power. While the direct participation of business leaders in the electoral contest in Mexico tends to be solely the work of individuals who are relatively dominated in the economic field, the shareholders of the country’s main multinationals seek to align themselves with the influence practices of the large groups of the global North and prefer more discreet strategies of influence on public policies.